PEMBENTUKAN TUNAS Lilium sp. SECARA EX VITRO DAN IN VITRO - Hoesen, Djadja Siti Hazar (Jurnal Teknologi Lingkungan, 2009)
Buds, planlets and bulblets formation from excised bulbscales was the preferredmethod for vegetative propagation of Lilium sp (Liliaceae). The ex vitro techniqueswith Gibberellic acid (GA3) pretreatment was induced buds formation on scalescutting which planted on sterilized sand media. Buds rised from basal scales 7days after planted. However scales untreated GA3 obtained in 35-42 after planted.In vitro methods to promote buds initiated from bulbscales explants, was inducedon media MS (Murashige and Skoog) supplemented with GA3 1 mg/l. Media forinduced buds formation, MS contained Benzyl adenine (BA) 1 mg/l and 2 mg/lincreased multiple shoots formation significantly compared cultured on mediawithout BA. Roots growth improved on media contained NAA, but the highestplanlets achieved on cultured MS media without BA. Bulblets formation obtainedon media contained higher concentration of BA (5 mg/l).